Investigation the changes of respiratory parameters in chemical veterans in different body positions - A. Mostafaloo; H. Daneshmandi; F. Rahmaninia; M. Akbar; S. Khosrojerdi (Afarand Scholarly Publishing Institute, 2011)
Purpose: The purpose of this investigation was to study the respiratory parameters in different body positions (standing, chair-sitting, supine and side-lying) in chemical veterans. Methodology: 10 chemical veterans (age 42.7±5 yrs height 174.8±5.4 cm weight 80.8±6 kg) participated in this study. Respiratory parameters such as Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 second (FEV1), Tidal Volume (TV), Peak Expiratory Flow (PEF), Minute Ventilation (VE), Breathing Frequency (fb) and FEV1/FVC ratio were measured by spirometer in different body positions. ANOVA with repeated measure was used to show the mean difference in each parameter between body positions. Results: The results showed no significant difference in any respiratory parameters between different body positions. Conclusions: Educating chemical veterans and they putting in proper body position can have a positive effect on pulmonary function and also, putting in improper body positions lead to occur variety of musculoskeletal problems that can have more effect on pulmonary system in chemical veterans.